Modified totally tubeless percutaneous nephrolithotomy: Is it an effective and safe treatment option for renal and upper ureteral stones? - Ho Seok Chung; Seung Il Jung; Ho Song Yu; Eu Chang Hwang; Kyung Jin Oh; Dong Deuk Kwon; Kwangsung Park (Videosurgery and Other Miniinvasive Techniques)
Introduction: We hypothesized that modified totally tubeless percutaneous nephrolithotomy (PNL) without indwelling ureteral stent would minimize postoperative discomfort without complications. Aim : To evaluate the safety, efficacy, and morbidity of standard, tubeless, and modified totally tubeless PNL as well as the usefulness of modified totally tubeless PNL. Material and methods: From November 2011 to February 2015, 211 patients who underwent PNL consecutively were enrolled in this study and divided into 3 groups (group 1: standard, group 2: tubeless, group 3: modified totally tubeless PNL). Patient and stone characteristics, operation time, hemoglobin change, length of hospitalization, stone-free rate, analgesic requirement, and perioperative complications were analyzed and compared among the 3 groups. Results: There were no significant differences in preoperative patient characteristics among the three groups. In the postoperative analysis, the three groups had similar operation time, stone-free rate, perioperative fever and transfusion rate, but group 2 showed superior results in terms of length of hospitalization (p = 0.001). Group 2 and group 3 had a lower analgesic requirement (p = 0.010). Immediate postoperative hemoglobin change (p = 0.001) and tube site complications (p = 0.001) were more common in group 1. Conclusions : Modified totally tubeless PNL was not inferior in terms of postoperative outcomes and safety compared with the standard and tubeless PNL, and avoided the postoperative stent-related symptoms and cystoscopy for double-J stent removal. Modified totally tubeless PNL could be an alternative treatment of choice for management of renal or upper ureteral stones in selected patients.